Effect of sulfur particle morphology on the performance of element sulfur-based denitrification packed-bed reactor. (January 2023) - Dong, Heng; Sun, Yi-Lu; Sun, Qi; Zhang, Xue-Ning; Wang, Hong-Cheng; Wang, Ai-Jie; Cheng, Hao-Yi
Graphical abstract: Highlights: Surface roughness only affected denitrification performance at start-up stage. Particle shape significantly affected denitrification performance at steady stage. Shape difference of particle resulted in the variation of AHRT and effective ω. A new proposed half-order kinetic model well explained the shape variation effect. Abstract: The effect of particle morphology on denitrification performance in element sulfur-based denitrification (ESDeN) packed-bed process is a gap. In this study, three different types of commercial sulfur particles were selected to build the ESDeN reactors. The results showed the reactors filled with rougher sulfur particles took shorter time to reach stable denitrification performance in the start-up stage. The reactors filled with cap-shape sulfur particles received the maximum nitrate removal rate of 849.49 ± 79.29 g N m −3  d −1 at empty bed contact time of 0.50 h, which was 2.34 times higher than that with ball-shape sulfur particles in the steady stage. The superior denitrification performance in the cap-shape particles set linked to its larger effective volumetric surface area (ωe, 1.67 times larger) and to the longer actual hydraulic retention time (AHRT, 1.80 times longer). This study extends the knowledge of the dependency of sulfur particle properties on denitrification performance in ESDeN packed-bed reactor.